THE PERFECTING OF THE ROMANIZATION PROCESS AND ITS INFLUENCE ON THE MUSICAL LIFE IN THE REPUBLIC OF MOLDOVA - Stela GUŢANU (Studia Universitatis Babeş-Bolyai. Musica)
The spiritual history of the Republic of Moldova has been permanently marked by an original and ancient musical art, incorporated in an infinite array of emotions. With roots in the most ancient times, new musical strata were added to the folk melos, in time, multiplying and continually diversifying the musical landscape. The Byzantine music is the essential part of Moldova’s artistic and cultural past. It has been the stepping stone in the development of the Romanian sacred music. Being a part of the Romanians’ cultural past, it has developed and has been transmitted from generation to generation, in their own traditional spirit.